DRES-13. DUAL KINASE INHIBITION TO COMBAT EGFR-INHIBITOR RESISTANCE IN GLIOBLASTOMA. (11th November 2019) - Smithberger, Erin; Shelton, Abigail; Butler, Madison; Flores, Alex; Bash, Ryan; Angus, Steven; East, Michael; Sciaky, Noah; Dhruv, Harshil; Johnson, Gary; Berens, Michael; Furnari, Frank; et al.
Abstract: Glioblastoma (GBM) is an aggressive primary brain tumor with a poor survival rate. One of the most common molecular alterations seen in GBM is amplification and/or mutation of the Epidermal Growth Factor Receptor (EGFR), which has made it an attractive therapeutic target. However, several EGFR tyrosine kinase inhibitors have been tested clinically in GBM with minimal success. One reason for this lack of efficacy could be due to acute, adaptive resistance via alternative pathway activation. To investigate this mechanism of tumor resistance, we used RNA-seq and multiplex inhibitor bead/mass spectrometry (MIB-MS) to analyze the transcriptomes and kinomes of genetically engineered murine astrocytes with common GBM genotypes. We have previously shown that 38% of the expressed kinome varied among a panel of diverse nGEM astrocytes harboring Cdkn2a deletion (C) plus Pten deletion (CP), wild-type human EGFR (CE) or EGFRvIII (CEv3) overexpression or both EGFRvIII overexpression and Pten deletion (CEv3P). Although CE have a similar transcriptional profile to C cells at baseline, when treated with the EGFR inhibitor afatinib, CE respond more similarly to CEv3 cells. When cells containing endogenous murine EGFR (C and CP) are treated with afatinib, fewer than 0.5% of kinases showed differential expression. In cells with EGFR overexpression alone, more than 6% of kinases were differentially expressed upon afatinib treatment, including Ntrk3, Fgfr2 and 3, Lyn, Bmx, Epha2 and 5, Fn3k, a kinase involved in fructosamine processing, and Nrbp2, a kinase involved in regulation of apoptosis. This effect was blunted in cells lacking Pten in addition to having EGFRvIII (CEv3P), resulting in less than 2% of kinases being differentially expressed. The only kinase upregulated in all three EGFR-overexpressing cell types was Coq8a, which is involved in electron transport and response to DNA damage. Given this overlap in response, Coq8a could be a potential dual treatment target for GBM.